(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
Female Genital Tuberculosis is a unique diagnostic challenge among the infertile population in countries where TB poses a high epidemiological risk. Early diagnosis and effective management is crucial to secure the reproductive organs from irretrievable damage. This cross sectional study was done between April 2011 to March 2012 in the Department of Microbiology and Immunology, Bangabandhu Sheikh Mujib Medical University in collaboration with National Tuberculosis Reference Laboratory and TB laboratory of International Centre for Diarrhoeal Disease Research, Bangladesh to compare the different laboratory tests on endometrial tissue for the diagnosis of genital tuberculosis. Laparoscopic endometrial tissue biopsies of 91 infertile women with clinical suspicion of Genital Tuberculosis were subjected to AFB smear microscopy, culture in Lowenstein Jensen media, histopathology and PCR assay. Two primers - mpt64, IS6110 were used as target for Mycobacterial DNA. Among the endometrial tissue samples of 91 infertile cases, AFB smear was positive in 43 (47%) cases, 8 (7.6%) cases was positive in culture; while PCR was positive in 36 (42.4%) cases. None of the cases were positive for epithelioid granulomatous lesions. PCR was found positive in 33% of smear negative cases and 35% of culture negative cases while PCR was found negative in 53.4% of smear positive cases and 12.5% of culture positive cases. Use of both AFB smear microscopy and PCR assay enhances the detection rate of GTB. Bangladesh J Med Microbiol 2014; 08 (02): 03-07